Risk factors for postoperative endoscopic recurrence in Crohn's disease: a Brazilian observational study - Barcelos,Ivan Folchini de (2014)
Introduction: Postoperative endoscopic recurrence (PER) is the initial event after intestinal resection in Crohn's disease (CD), and after a few years most patients present with progressive symptoms and complications related to the disease. The identification of risk factors for PER can help in the optimization of postoperative therapy and contribute to its prevention. Methods: Retrospective, longitudinal, multicenter, observational study involving patients with CD who underwent ileocolic resections. The patients were allocated into two groups according to the presence of PER and the variables of interest were analyzed to identify the associated factors for recurrence. Results: Eighty-five patients were included in the study. The mean period of the first postoperative colonoscopy was 12.8 (3–120) months and PER was observed in 28 patients (32.9%). There was no statistical difference in relation to gender, mean age, duration of CD, family history, previous intestinal resections, smoking, Montreal classification, blood transfusion, residual CD, surgical technique, postoperative complications, presence of granulomas at histology, specimen extension and use of postoperative biological therapy. The preoperative use of corticosteroids was the only variable that showed a significant difference between the groups in univariate analysis, being more common in patients with PER (42.8% vs. 21%; p = 0.044). Conclusions: PER was observed in 32.9% of the patients. The preoperative use of corticosteroids was the only risk factor associated with PER in this observational analysis.